PERANAN KOMODITAS JAGUNG (Zea mays L.) TERHADAP PENINGKATAN PENDAPATAN WILAYAH KABUPATEN KARO - Ivan Setyastiawan; Teguh Wahyono; Yusniar Lubis (Universitas Medan Area, 2018)
Corn is a commodity whose role is increasingly important both as a food or raw materials of food industry, as well as animal feed raw materials, and a multipurpose commodity which has a lot of derivative products when processed estimated 2-3% for domestic consumption and the rest for the industry even overseas corn used as a biofuel. The are very big demand of global for the corn, with a huge potential increase in supply and demand world, it is estimated that there are great opportunities to develop agribusiness corn in North Sumatra.The are very big potential on corn development at North Sumatra, but the real production of corn is still far below its demand, so that the corn needs are not always met. The corn agribusiness development at Karo Regency is expected to boost the regional economy, rural employment, increase the farmers' income. The corn cultivation had influence on regional development in Karo Regency, the increase in income area with an average contribution of 6.14%. The corn cultivation at Karo Regency is the economic basis based on income indicators. Keywords : Corn, GDP, production.